2014
DOI: 10.7589/2013-09-232
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Seasonal Patterns in the Relative Abundance of Avian Influenza Virus Subtypes in Blue-Winged Teal (Anas discors)

Abstract: Seasonal dynamics of influenza A viruses (IAVs) are driven by host density and population immunity. Through an analysis of subtypic data for IAVs isolated from Blue-winged Teal (Anas discors), we present evidence for seasonal patterns in the relative abundance of viral subtypes in spring and summer/autumn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 20 publications
3
36
0
Order By: Relevance
“…Prevalence estimates based on rRT-PCR for northern shovelers and blue-winged teals are higher than reported in wintering populations in other geographical regions (7, 19). Overall prevalence estimates based on virus isolation for blue-winged teals (5.7%) and northern shovelers (4.7%) are comparable with studies from wintering ducks in California and Louisiana (19, 37, 43). A higher prevalence based on rRT-PCR is not surprising, as only rRT-PCR positive samples were tested for virus isolation.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Prevalence estimates based on rRT-PCR for northern shovelers and blue-winged teals are higher than reported in wintering populations in other geographical regions (7, 19). Overall prevalence estimates based on virus isolation for blue-winged teals (5.7%) and northern shovelers (4.7%) are comparable with studies from wintering ducks in California and Louisiana (19, 37, 43). A higher prevalence based on rRT-PCR is not surprising, as only rRT-PCR positive samples were tested for virus isolation.…”
Section: Discussionsupporting
confidence: 63%
“…H5 viruses were isolated in November in 2010, December in 2012, and in January in 2013, whereas the H7 viruses were only detected in January, in the 2011-12 and 2012-13 seasons. Three H14 viruses were recovered during the 2011-2012 season (37), and during the 2012-13 season the H14 was the most prevalent subtype, detected in November (8 of 21 isolates) and January (4 of 7 isolates).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the H4 and H6 subtypes were also frequent in surveillance studies in Europe, recurrent detection of other subtypes was not significantly different [5, 13]. Seasonal patterns of IAV prevalence among wild birds have been described; however, factors and mechanisms that drive diversity and prevalence of IAV subtypes such as the effects of homo- and heterosubtypic immunity remain unclear [14, 15]. Previous studies have demonstrated the induction of homosubtypic and partial heterosubtypic immunity in mallards [1620], and this has been supported further by field observations [21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although active surveillance for IAV in wild birds has been conducted with increased intensity during the past decade, including areas within the Mississippi Flyway, most sampling efforts have been focused in autumn when viral prevalence has previously been reported to be highest; however, this sampling bias may have contributed to incomplete reference data for the genetic diversity of H7 subtype viruses circulating in wild birds in North America prior to the 2009 and 2011 outbreaks in domestic turkeys. Recent evidence suggests that viruses of the H7 subtype may be relatively more abundant at locations within the Mississippi Flyway during spring (Ramey et al, 2014), a season during which active surveillance for IAV in wild birds has been limited. Thus, increased surveillance efforts during this season may be useful for assessing spill-over of IAVs of the H7 HA subtype between wild birds and poultry.…”
Section: Discussionmentioning
confidence: 99%